(3EfHGA GdZeQ HCHfGA GdYeQs - (3CMeO Hf Ydj Hf eMeO GdcfGfj GdYSbdGfj, CHh GdaVd, TgGH GdOjf, GHf nMnLQ,J (B852 (3g` s
(3ChdgG (B:s
(3CeG HYO ajbhd GdYHO GdVYja CMeO Hf MLQ GdYSbdGfi gPG JYdjb MOK ajg MhGOK GdReGf s
(3BNQgG (B:s
(3ef LeGd GdOjf GdfGUQ bHdg abJdg hcGfJ dg eYQaI hgeI YGdjI s
(3fSNI KGfjIs
(3hgj eShOI GdeDda cJHJ ai CRefI eNJdaI BNQgG SfI (B850s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B35 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs